1986
DOI: 10.1002/jcu.1870140902
|View full text |Cite
|
Sign up to set email alerts
|

A composite three‐dimensional echocardiographic technique for left ventricular volume estimation in children: Comparison with angiography and established echographic methods

Abstract: A composite three-dimensional (3D) echographic left ventricular (LV) reconstruction to measure LV volumes was evaluated in 26 children. Four apical views, to minimize assumptions about LV shape, were used to obtain a "wire-cage" model of the LV in 3D. Numerical integration was used to make estimates of both end-diastolic and end-systolic volumes. Volume estimates obtained with echographic techniques and those obtained with the angiographic biplane method were compared. The echographic volume estimates were sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…During diastole (P6-P9), moderate or small magnitudes can be observed. The velocity of the wall of the LV is shown in Table 4,7,20 The ejection fraction (EF: the percentage of blood that leaves the heart with each beat) is computed according to the following formula:…”
Section: Resultsmentioning
confidence: 99%
“…During diastole (P6-P9), moderate or small magnitudes can be observed. The velocity of the wall of the LV is shown in Table 4,7,20 The ejection fraction (EF: the percentage of blood that leaves the heart with each beat) is computed according to the following formula:…”
Section: Resultsmentioning
confidence: 99%
“…In 3D echocardiography, the entire heart can be reconstructed in three dimensions from several short‐ and long‐axis images 32 . LV mass is then calculated based on the volume of the ventricle rather than on thickness of its walls and internal diameter 33–41 . Thus, this technique is not limited by the assumptions concerning LV geometry and symmetry and by errors in image plane positioning 41–46 …”
mentioning
confidence: 99%
“…32 LV mass is then calculated based on the volume of the ventricle rather than on thickness of its walls and internal diameter. [33][34][35][36][37][38][39][40][41] Thus, this technique is not limited by the assumptions concerning LV geometry and symmetry and by errors in image plane positioning. [41][42][43][44][45][46] This study examined the hypothesis that one of the reasons for the reported low sensitivity of various ECG criteria in detecting LVH is overestimation of LV mass by M-mode and 2D echo measurements.…”
mentioning
confidence: 99%